Causes &clinical presentation of hypotonia in children - AL-Naddawi, Mahjoob N.; Mussa, Russul F.; kamel, Khawla M. (Journal of the Faculty of Medicine Baghdad, 2010)
Background: Hypotonia is not a specific medical disorder, but a potential manifestation of many different diseases and disorders. The long-term effects of hypotonia on a child's development and later life depend primarily on the severity of the muscle weakness and the nature of the cause.Patients &Methods: A prospective, cross sectional descriptive study in which 62 patients with hypotonia, age 3months to13 years, were evaluated in children welfare teaching hospital /Baghdad (a tertiary care center), over 4months Period (1st of January to 1st of May,2008 ) . Children were categorized into groups of central , peripheral& systemic hypotonia, and specific diagnosis of each of groups was made by clinical findings, neuroimaging, metabolic, muscular enzymes, Electromyography-Nerve conduction velocity, thyroid function tests, Serum Calicium&X- RAY of left wrist,& TORCH (Toxoplasmosis,others, rubella, CMV, herps simplex) assay in our medical teaching laboratories.Results: The most common cause of hypotonia was central in 30 patients (48.4 %). (Four patient with unknown causes), the most common lesion was brain atrophy detected by CT scan examination in 23/30 (76.7%). Peripheral causes found in 14/58 (22.6%) which include myopathies in 7 patients (11.3%), anterior horn cell lesion in 7 patients (11.3%). Systemic causes were found in 14/58 (22.6%). Early Onset in 46/62 (74.2%), while late onset constituted 16/62 (25.8%).The most common mode of presentation is delayed mile stones found in 32 patients (51.6%).Conclusions: The most common cause of hypotonia in children enrolled in the study is central lesion and commonly occurs in pre natal, natal & post natal periods. The most common finding is brain atrophy diagnosed by CT scan, while the most common presentation is delayed milestones, and most common type of weakness is proximal.